PENGARUH PENGGUNAAN ABU TERBANG (FLY ASH) SEBAGAI BAHAN TAMBAH TERHADAP KUAT TEKAN MORTAR - Azizah, Titanya; Wahyuni, Ade Sri; Islam, Mukhlis; Gunawan, Agustin; Afrizal, Yuzuar (Inersia: Jurnal Teknik Sipil, 2022)
Mortar is material used in non-structural elements. The increasing of quality of the mortar can be obtained by adding other alternative materials to its constituent materials. The materials that have pozzolan characteristic can increase the compressive strength of the mortar. Fly ash has a pozzolan characteristic and contains silica so that it can be used as an additive to cement. This study aims to know the compressive strength of mortar by using fly ash as the additional material of cement with the ratio of cement to fine agregate were 1pc : 3ps on 14, 21, and 28 days. The sample of the mortar is a cuboid sized 50mm x 50mm x 50mm. The variations of fly ash used were 5%, 10%, 15%, and 20% with 7 samples in each variations. The range of initial flow values was between 105%-115% (SNI 03-6882-2002). The biggest compressive strength value for normal mortar is 11.15 MPa and the biggest compressive strength for the variation of mortar is 14.43 MPa at 15% variation at 28 days. The percentage increase in the compressive strength of the mortar is 29,48% from normal mortar.